Enterprise architecture-based ISA model development for ICT benchmarking in construction-case study - Ehab Juma Adwan; Ali Al-Soufi (Institute of Advanced Engineering and Science, 2022)
Building on a coincided in progress paper, this paper constructs and evaluate an information systems architecture (ISA) model for the Bahraini architecture, engineering and construction (AEC) sector, from the lens of enterprise architecture (EA). This model acts as an information and communication technology (ICT) barometer tool to identify and benchmark the ICT’s gaps, duplicative levels, and future investments. Following the design science research, this paper and throughout a utilization of a tailored version of the open group architectural framework (TOGAF), embedded into a rigorous case study approach, the construction, testing, and evaluation of the conceptual ISA model is approached to benchmark the ICT measurement. Empirically, the study revealed the appropriateness of the model and the ability to identify the availability of 28 groups of 38 individual ICT applications in the Bahraini AEC sector and benchmark them to score an average of 18.5% against 17 countries that scored an average of 18.6%.